The Sociology of Healthcare : A reader for health professionals - Earle, Sarah, 1972-; Letherby, Gayle (Basingstoke : Palgrave Macmillan, 2008)
A comprehensive collection of classic and contemporary readings in the sociology of health, this title will stimulate debate, reflexive practice and critical thinking in applied sociology and is aimed at the teaching and learning needs of both lecturers and students.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Social medicine